The Role of Spinal Orthoses in Osteoporotic Vertebral Fractures of the Elderly Population (Age 60 Years or Older): Systematic Review. Issue 6 (July 2021) - Kweh, Barry Ting Sheen; Lee, Hui Qing; Tan, Terence; Rutges, Joost; Marion, Travis; Tew, Kim Siong; Bhalla, Vikram; Menon, Shyaman; Oner, Fetullah Cumhur; Fisher, Charles; Tee, Jin Wee
Study Design: Systematic review. Objective: Spinal orthoses have been generally used in the management of osteoporotic vertebral fractures in the elderly population with purported positive biomechanical and functional effects. To our knowledge, this is the first systematic review of the literature examining the role of spinal orthoses in osteoporotic elderly patients who sustain low energy trauma vertebral fractures. Methods: A systematic literature review adherent to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines was conducted. Methodical searches utilizing MEDLINE, EMBASE, Google Scholar, and Cochrane Databases was performed. Results: Of the 2019 articles initially retrieved, 7 published articles (4 randomized controlled trials and 3 prospective cohort studies) satisfied the inclusion criteria. Five studies reported improvement in quantitative measurements of spinal column stability when either a rigid or semirigid orthosis was used, while 1 study was equivocal. The studies also showed the translation of biomechanical benefit into significant functional improvement as manifested by improved postural stability and reduced body sway. Subjective improvement in pain scores and quality of life was also noted with bracing. Conclusion: The use of spinal orthoses in neurologically intact elderly patients aged 60 years and older with osteoporotic compression vertebral fractures results in improved biomechanical vertebral stability, reduced kyphotic deformity, enhanced postural stability, greater muscular strength and superior functional outcomes.